Econometric Modelling On Satisfaction In Rice Farming Under Philippine Rice Tariffication Law - Leomarich F Casinillo (Lembaga Sembilan Tiga Community, 2020)
This study focused on the farmers’ satisfaction and its influencing determinants under the implementation of Rice Tariffication Law (RTL) in Leyte, Philippines. Currently, very limited studies are available in literature regarding the Law. Hence, this study is conducted to evaluate the farmers’ satisfaction while experiencing the Law. With the aid of probabilistic sampling method, the study employed 169 rice farmers as the participants. A developed questionnaire was used to gather primary data and analyzed using descriptive statistics and econometric modelling. Results showed that the farmers’ actual satisfaction is relatively lower compared to expected satisfaction. This is due to negative effects of RTL. The study documented a significant socio-demographic determinants of satisfaction in farming, namely: gender, marital status, education and rice farm ownership. Income from rice farming has inverse effect on satisfaction. Farmers with high income also experience high expenses in agricultural inputs which negatively affects their well-being. A low other monthly income of farmers has a chance of being satisfied in rice farming. Satisfied farmers spend more time in farming and results to higher opportunity cost for other income activities. Furthermore, household consumption, household assets, and household expense positively affects satisfaction of farmers due to the benefits and comfort.